1972
DOI: 10.1111/j.1471-0528.1972.tb12899.x
|View full text |Cite
|
Sign up to set email alerts
|

A Case Control Study Into the Possible Effects of Birth Control Pills on Pre‐clinical Carcinoma of the Cervix

Abstract: This paper reports a study of the possible relationship between oral contraceptives and preclinical squamous carcinoma of the cervix in women in their third decade in the Province of British Columbia. A total of 310 cases of preclinical carcinoma of the cervix and 682 matched controls were evaluated. The mean interval between first use of contraceptives and entry into the study was 5.3 years for the 25-29year-old patients with preclinical carcinoma of the cervix, while the interval for the 20-24-year-old patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

1977
1977
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(10 citation statements)
references
References 4 publications
3
7
0
Order By: Relevance
“…The reported effect has, however, usually been small. Worth and Boyes (1972) Our data clearly strengthen the evidence that use of the diaphragm is associated with a reduced risk of cervical neoplasia. In this context, it is important to note that the diaphragm users in our study had mostly had long experience of the method; at the time of entry to the study over half of them had persisted with this method of birth control for 5 or more years (Vessey et al, 1976).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The reported effect has, however, usually been small. Worth and Boyes (1972) Our data clearly strengthen the evidence that use of the diaphragm is associated with a reduced risk of cervical neoplasia. In this context, it is important to note that the diaphragm users in our study had mostly had long experience of the method; at the time of entry to the study over half of them had persisted with this method of birth control for 5 or more years (Vessey et al, 1976).…”
Section: Discussionsupporting
confidence: 83%
“…Many authors have obtained data which suggest that this is so (Boyd and Doll, 1964;Melamed et al, 1969;Worth and Boyes, 1972;Boyce et al, 1977;Collette et al, 1978). The reported effect has, however, usually been small.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the pooled relative risk for cervical abnormalities (mostly displasia or in situ carcinoma) from seven casecontrol studies or prospective investigations analysed as case-controls conducted in North America, Britain and Czechoslovakia (Thomas, 1972;Worth and Boyes, 1972;Boyce et al, 1977;Ory et al, 1977;Harris et al, 1980;Vonka et al, 1984; WHO Collaborative Study on Neoplasia and Steroid Contraceptives, 1985) and based on a total of over 20,000 subjects was 1.1 (Franceschi et al, 1986) thus indicating no or a very limited material overall elevation of risk in oral contraceptives users. It may also of interest to note that, in the present study, women who had ever used oral contraceptives did not have a larger number of sexual partners than those using other or no contraceptive method, but they did report more frequent screening 'Pap' smears, which have been reported to reduce risk of cervical cancer (La Vecchia et al, 1984b).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the remaining studies (which have dealt with histologically diagnosed lesions) have been well reviewed by a World Health Organization Scientific Group (1978). Of the case-control studies, those by Worth & Boyes (1972), Thomas (1972) and Boyce et al (1977) indicated no relation, while those by Ory et al (1977) andHarris et al (1980) showed a positive association between risk and duration of use. Cohort studies of cervical neoplasia and the pill have tended to produce positive results.…”
Section: Administration Of Hormones To Prevent Pregnancymentioning
confidence: 99%